Age-specific effects of synthetic cannabinoids on cognitive function and hippocampal gene expression in mice: insights from behavioral and molecular correlates - Li, Kaixi; Chen, Yuanyuan; Xu, Yawen; Pang, Yuan; Bao, Yongli; Zhang, Simeng; Shi, Xuesong; Ran, Jingzhi; Qiao, Yanling; Xu, Yizhao; Wang, Yiming; Di, Bin; et al. (Frontiers in Pharmacology, 2025)
The increasing use of Synthetic cannabinoids (SCs) in adolescents and young adults poses significant medical and psychiatric risks, and previous reports have been dominated by single-age animal studies. Here, we first investigated the effects of a single exposure of the fourth-generation synthetic cannabinoid 4F-ABUTINACA on cognitive behaviors in adolescent (PND 28–35 days) and adult (PND 49–56 days) male mice in an animal model, followed by an age-specific systematic study by conducting a whole-gene transcriptomics study of hippocampal tissue in the brain. Behavioral results showed that 4F-ABUTINACA impaired recognition memory, fear memory extraction, and spatial navigation memory in adolescent mice, as well as spatial navigation memory in adult mice. The transcriptomics results revealed different alterations in age-enriched signaling pathways affected by 4F-ABUTINACA, such as Alzheimer’s disease, Parkinson’s disease, and neurodegenerative diseases. In addition, 4F-ABUTINACA causes selective downregulation of transcription of genes involved in stress response and mitochondrial expression in adolescent mice, whereas no significant differences were observed in adult mice. This study provides an innovative resource on the behavioral and molecular landscape of age-specific changes in cognitive function by synthetic cannabinoids and offers new opportunities for follow-up studies to target age-specific functional significance and related molecular mechanisms to be mined.